Performance management of a service unit in hotel theoretical review - Ala`a Nimer, Mousa Abukhalifeh; Mat Som , Ahmad Puad (2013)
This paper aims to review the existing literature on performance management in the F&B department of hotels, its processes, and its effective management system framework. This paper discusses food and beverage systems and explains a system model framework of performance management in the area of F&B and its application to the hotel industry. The conceptual paper suggests an application of the system model in the F&B department and encourages hotels to improve its management to better serve their guests.